Peningkatan Kemampuan Menulis Kalimat Efektif Melalui Metode Penugasan di Sekolah Menengah Pertama - Arozatulo Bawamenewi (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study was to improve students' ability to write effective sentences through the assignment model. Writing is a thinking process skill in expressing ideas that are poured in written form to describe something (imaginative and factual). This thinking process includes the process of how ideas are generated, and is focused on certain ideas that are relevant and interrelated. Often found in learning, especially in Indonesian lessons, when the teacher asks students to write a sentence in front of the class, many students are less able to write both in terms of diction and in terms of the written language, this happens because students lack practice and do not have motivation. in doing activities in writing. Therefore, teachers need to find solutions to solve the problems mentioned above by using one of the learning methods, namely by using the assignment method to improve student learning outcomes in using effective sentences. Based on the problems mentioned above, the researchers are interested in raising the title of scientific research "Improving the Ability to Write Effective Sentences through the Assignment Method for Students